Dimensions and Sub-Dimensions for the Evaluation of M-Learning Apps for Children: A Review - Hussain, Azham; O.C. Mkpojiogu, Emmanuel; Hassan, Fa’alina (International Journal of Engineering and Technology, 2018)
The introduction and rapid growth of mobile learning applications (m-learning apps) has improved the role of teachers in facilitating the learning process especially among children. The learning experiences of children are enhanced and enriched with the use of m-learning apps for children. There are several m-learning apps developed for children in the market today, however, some of these apps do not succinctly support and adequately assist in the learning process and educational endeavors and quest of these young minds. In this paper, a systematic review of literature was conducted to assess past research and studies on usability dimensions and sub-dimensions utilized in evaluating children’s m-learning apps. The systematic literature review consisted of the following approach: the definition of search strategy, selection of primary studies, data extraction, and implementation of synthesis strategy and lastly, the presentation of findings. The result of the review reveals that effectiveness, efficiency, learnability, and user satisfaction (with their corresponding sub-dimensions) were the top four usability dimensions used in the evaluation of m-learning apps for children. In addition, the works reviewed showed that usability evaluation is prominent only during the implementation phase of the applications’ development.